Post-partum posterior reversible encephalopathy syndrome - B. V. Triveni; Salman Mohammed Sheikh; Deepak Shedde (Wolters Kluwer Medknow Publications, 2014)
Posterior Reversible Encephalopathy Syndrome (PRES) is a clinicopathological syndrome associated with various clinical conditions presenting with headache, encephalopathy, seizure and cortical visual disturbances. Radiological findings in PRES are thought to be due to vasogenic edema predominantly in posterior cerebral hemispheres and are reversible with appropriate management. We present a case of post partum PRES,A 29 year old primigravida of 33 weeks 3 days period of gestation who presented to our hospital with painless bleeding per vagina and breathlessness. A provisional diagnosis of Ante partum Haemorrhage due to Marginal Placenta Previa was made and she was admitted for safe confinement. Caesarean section was performed for APH under subarachnoid block which was uneventful. On the fourth post operative day patient developed headache and generalised tonic clonic seizures. The provisional diagnosis of Postpartum PRES was made and confirmed with MRI. All other causes of postpartum seizures were ruled out. Patient was successfully treated with anticonvulsants, corticosteroids and supportive treatment Postpartum PRES is a rare clinical condition mostly associated with hypertension, Preeclampsia and vasculitis .Early recognition and treatment can lead to complete recovery of the condition